2016
DOI: 10.4028/www.scientific.net/ssp.249.79
|View full text |Cite
|
Sign up to set email alerts
|

Basalt Fibers as New Material for Reinforcement and Confinement of Concrete

Abstract: Basalt Fibre Reinforced Polymer (BFRP) is a new material in civil engineering and has shown to be a promising material for infrastructure strengthening. In comparison to carbon fiber, glass fiber and other composites, it has some advantages such as high-temperature resistance and low cost. At the Structural and Composite Laboratory at Reykjavik University (SEL) several research projects involving strengthening concrete beams and columns by using FRP materials have been on-going in recent years. These tests hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…Thus, pre-tensioning can compensate for the lower flexural rigidity of beams reinforced by flexural BFRP reinforcement as compared with traditional reinforced concrete beams. This conclusion agrees with previous results obtained by finite element simulation [38] and experimental testing of BFRP-reinforced concrete beams [21,22,39,40].…”
Section: Numerical Resultssupporting
confidence: 93%
“…Thus, pre-tensioning can compensate for the lower flexural rigidity of beams reinforced by flexural BFRP reinforcement as compared with traditional reinforced concrete beams. This conclusion agrees with previous results obtained by finite element simulation [38] and experimental testing of BFRP-reinforced concrete beams [21,22,39,40].…”
Section: Numerical Resultssupporting
confidence: 93%
“…In the case of TSPC, there was no available FEM found in the previous literature, which make the process of TSPC modeling become troublesome as there were no baseline parameters to be referred. Therefore, there was a potential Previous study on cement concrete structures has reported the confinement of concrete structure using aramid fiber (Yang et al 2015), basalt fiber (Thorhallsson and Snaebjornsson 2016;Nabi et al 2019;Yang et al 2018), and steel tube (Kedziora and Anwaar 2019;Tao et al 2013). All of these studies have provided new fundamental data contributing toward the concrete structure design for strengthening purpose.…”
Section: Discussion and Suggestionmentioning
confidence: 99%
“…Major advantages associated with natural fibers include low cost, low density, high toughness and biodegradability. Among the natural fibers, basalt fibers are attracting significant interest due to good sound insulating properties, good heat resistance (superior to glass), excellent protection from chemical attack, and low water absorption properties [ 1 ]. High heat resistance of basalt is useful for applications requiring thermal insulation as for hot fluids transportation pipes.…”
Section: Introductionmentioning
confidence: 99%